A method for complex spatial delimitation of tourism destinations in South Transdanubia - Aubert, Antal; Csapó, János; Pirkhoffer, Ervin; Puczkó, László; Szabó, Géza (Hungarian Geographical Bulletin, 2010)
As a special segment of the research of the interrelated system of tourism and regional development, the present study is aimed to deal with and focus on the methods of the regional delimitation of spaces and areas of tourism based on its supply and demand aspects, providing recent data on this rather neglected field. Following the general introduction of the study area (South Transdanubia, Hungary), the research background with a literature review of the international practice on the given topic is presented. The main portion of the paper is the introduction of a new method elaborated by our research group concerning the demarcation possibilities of core/periphery areas of tourism, among others using GIS methods. This method provides a fairly accurate approach for centre–periphery research concerning the study of tourism.